Elder abuse and mistreatment: results from medicare claims data. Issue 4 (20th October 2019) - Mouton, Charles P.; Haas, Allen; Karmarkar, Amol; Kuo, Yong-Fang; Ottenbacher, Kenneth
ABSTRACT: Elder abuse and mistreatment (EM) continues to be a growing problem as the US population ages. Despite the growth, detection of EM continues to lag. However, Medicare claims data and the electronic health record might provide an opportunity to encourage better detection. We evaluated Medicare claims data from 2012–2014 for beneficiaries who had a diagnostic code for EM discharged from any types of facility. We extracted records for 10, 181 individuals examining demographic characteristics, residential characteristics, residential location, type of facility providing care, disease co-morbidities, and disability-related conditions. Of our sample, most were female (65.1%), white (78.8%), over 75 years of age (52.6%), and from an urban setting (85.2%). While the greatest number were discharged from acute care settings, almost one-third were hospitalized in psychiatric hospitals (34.6%). Mood disorders (27.5%) and dementia (14.2%) were the most common primary diagnoses. Hypertension (67.7%), depression (44.6%), fluid and electrolyte disorder (43.6%), and cardiac arrhythmia (28.2%) were the most common co-morbidities. In Medicare claims data, we found unique features and co-morbidities associated with EM. These findings could be used to develop a clinical algorithm predictive of older adults requiring screening for EM.